Stability analysis for yield and yield contributing characters in Groundnut (Arachis hypogaea L.): Stability analysis for yield and yield contributing characters in Groundnut (Arachis hypogaea L.) - K W KAMBLE; M V DHUPPE; A J SALUNKE; B KRISHNASRI (Journal of Oilseeds Research, 2023)
Twenty two genotypes including two checks were evaluated in randomized block design with three replications for yield and yield components under different environments. Estimates of stability parameters revealed that none of the genotypes were stable for all characters; however the genotype ICGV-07296 possesses average stability for days to maturity and pod yield per plant, where as the genotype ICGV-98170 recorded early flowering, where as the genotype ICGV-07273 for number of mature pod per plant, ICGV-07235 and ICGV-00187 for kernel yield per plant, ICGV-07273 for oil content exhibited average stability so they were adapted to all the environments. ICGV-07296 for days to maturity, ICGV-07273 for shelling percentage, ICGV-06151 for sound mature kernel, ICGV-06150 and ICGV-07217 for pod yield per plant and ICGV-0076 for pod yield per plot showed below average stability so they were better adapted to favorable environment. Whereas the genotypes ICGV-0211, ICGV-07270 and JL-24 were found especially adapted to better environment, while the genotypes ICGV-07106 and ICGV-06138 were adapted to unfavorable or poor environment.